Vytápění krytého bazénu - Musílková, Julie (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Tématem diplomové práce je vytápění krytého bazénu. Práce je rozdělena na tři části. V první části je teoreticky rozebraná problematika vnitřního prostřední bazénových hal. V druhé části je uvedena výpočtová část projektu. Projekt řeší vytápění krytého bazénu. V poslední části je řešen experiment, který se zabýval měřením teploty a relativní vlhkosti v bazénové hale.

Theme of diploma thesis is the heating of the indoor swimming pool. The thesis is departed to three parts. In the first part, there is a theoretical solution indoor climate of swimming pool. In the second part, there is a calculation solution of the project. Project solves heating of the indoor swimming pool. The last part is an experimental part. Theme of the experiment is measurement of temperature and relative humidity of the swimming pool.
Heating of the indoor swimming pool
Keywords: Diplomová práce; voda; vzduch; bazénová hala; předávací stanice tepla; desková otopná tělesa; deskový výměník; oběhové čerpadlo; termostatická hlavice; expanzní nádoba; pojistný ventil; Diploma thesis; water; air; swimming pool; heat transfer stations; radiators; plate heat exchanger; circulation pump; thermostat housing; expansion vessel; safety valve